2018
DOI: 10.1113/jp276414
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐regulation of haemostasis in hypoxic exercising humans: a randomised double‐blind placebo‐controlled antioxidant study

Abstract: In vitro evidence suggests that blood coagulation is activated by increased oxidative stress although the link and underlying mechanism in humans have yet to be established. We conducted the first randomised controlled trial to examine if oral antioxidant prophylaxis alters the haemostatic responses to hypoxia and exercise. Healthy males were randomly assigned double-blind to either an antioxidant (n = 20) or placebo group (n = 16). The antioxidant group ingested two capsules/day that each contained 500 mg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…There are other candidates that potentially impair cognitive performance during prolonged exposure to hypoxia. First, free radical formation increases under hypoxia . It has recently been suggested that systemic oxidative‐inflammatory‐nitrosative stress in high‐altitude residents is associated with accelerated cognitive decline .…”
Section: Acute Exercise Severity and Duration Of Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…There are other candidates that potentially impair cognitive performance during prolonged exposure to hypoxia. First, free radical formation increases under hypoxia . It has recently been suggested that systemic oxidative‐inflammatory‐nitrosative stress in high‐altitude residents is associated with accelerated cognitive decline .…”
Section: Acute Exercise Severity and Duration Of Hypoxiamentioning
confidence: 99%
“…First, free radical formation increases under hypoxia. 88,89 It has recently been suggested that systemic oxidative-inflammatory-nitrosative stress in high-altitude residents is associated with accelerated cognitive decline. 90 Furthermore, peripheral blood hypersensitive C-reactive protein, which is a biomarker of inflammation, is correlated with cognitive impairments during high-altitude expeditions.…”
Section: Duration Of Exposure To Hypoxiamentioning
confidence: 99%
“…That is, a probable increase in systemic free radicals, as supported by an increase in the VC radical, restored thrombin levels (Fall et al . ). The authors suggest that systemic free radical production is a hormetic phenomenon that contributes to physiological vascular haemostasis.…”
mentioning
confidence: 97%
“…In an article in this issue of The Journal of Physiology , Fall et al . () provide novel insight regarding the redox regulation of haemostasis in vivo in the exercising human.…”
mentioning
confidence: 99%
See 1 more Smart Citation